SIMULATION AND ANALYSIS OF RAYLEIGH BACKSCATTERING EFFECTS IN 105 KM LONG-REACH RSOA-BASED HYBRID WDM/TDM PON TRANSMISSIONS - Simatupang, Joni Welman (LIPI Press, 2013)
Passive Optical Networks (PONs)-based hybrid wavelength-division-multiplexing/time-division-multiplexing (WDM/TDM) technologies could be an excellent candidate for being used in the next-generation optical accessnetworks (NGOANs). However, Rayleigh backscattering (RB) effects can cause severe degradation on their performances while utilizing a single-fiber wavelength-reused loop-back confi guration (re-modulation technique) by employing Refl ective Semiconductor Optical Amplifi ers (RSOAs)-based as colorless upstream transmitters at optical network terminals (ONTs) or optical network units (ONUs). In long-reach PONs, optical amplifi cation is an indispensable solution; therefore optical amplifi ers are exactly needed to enhance the power budget and to prevent the fi ber non-linearity problem. As a proof-of-concept, crosstalk-to-signal (C/S) ratio as a function of feeder or distribution fi ber length is briefl y derived using analytical solution method and then simulated using MATLAB commercial software (R2008b) in order to determine the performance of three different architectures (topologies) of 105 km long-reach RSOA-based hybrid WDM/TDM PON transmissions. After the simulation and analysis, the best C/S ratio of -19 dB is obtained for the third topology. This topology even can serve up to 2048 users (subscribers). Users or subscribers could be at home (known as fi ber-to-the-home, FTTH technologies) or in the building(f ber-to-the-building, FTTB technologies).